A research on space morphology of Davao City downtown area an analytical approach in formation and transformation of a city center - Burlaza, Sharmane Joy M. (2016)
For the past years, Davao City has been experiencing a massive population growth due to the internal migration of people from neighboring rural areas and some far-flung parts of the country who are in search of job opportunities, more modern facilities and services, and the other things that Davao City offers. This means that more business establishments will be emerging in the city center to cater the demand from the growing population. The purpose of the research therefore, was to study Davao City Downtown Area?s formation, and transformation over the years to understand its current spatial structure, character and pattern of use in order to generate an efficient and effective plan of the city?s rapid and expanding urbanization. To trace the gradual processes of formation and transformation of the urban form, a complete representation of the spatial network was mapped out through the collection of historical maps and topographic maps of each decade from CPDO ( City Planning and Development Office) and through interviews of key informants in a form of cognitive mapping. Moreover, the political and socio-economic factors that influenced the changes of the land use and spatial configuration were also determined and were obtained through key informant interviews and focus group discussion. Space Syntax alpha Analysis was then used to quantify and analyze the spatial configuration of each period from 1950s to the present. This tool of analysis generated the integration cores of the spatial system. Using these data, the most suitable type of development for each part of the system was determined.